Advancing education-based mental health in low-resource settings during health crises: the mental health initiative of the University of the Philippines during the COVID-19 pandemic - Gonzalo, Richard Philip; Alibudbud, Rowalt (Frontiers in Education, 2024)
The COVID-19 pandemic exacerbated students' mental health challenges worldwide, including in the Philippines. This paper explores the University of the Philippines' response to this crisis, a crucial endeavor given the country's limited mental health resources. This paper reviews the relevant documents to the mental health initiative, titled "Sandigan, Sandalan," which sought to empower university stakeholders to advocate for mental and address mental health needs despite resource constraints and the university's vastness. The authors also share their experiences and insights in the program. This program is one of the few university mental health programs that were documented in the Philippines after the legislation of the Philippine Mental Health Act and during the COVID-19 pandemic. Key recommendations arising from this experience include enhancing program visibility, fostering stakeholder collaboration towards a clear set of program objectives, leveraging mental health expertise, empowering stakeholders, and designing replicable program models for the different campuses of the university. The initiative underscores the vital role that educational institutions can play and provides valuable insights into supporting students' mental well-being amid large scale challenges in low-resource settings.